Laser-induced breakdown spectroscopy for food authentication. (August 2019) - Markiewicz-Keszycka, Maria; Cama-Moncunill, Raquel; Pietat Casado-Gavalda, Maria; Sullivan, Carl; Cullen, Patrick J
Graphical abstract: Highlights: Elemental fingerprinting has been proven effective for authentication of certain foods. Laser-induced breakdown spectroscopy (LIBS) provide mineral fingerprint of food. LIBS allows rapid, high-throughput, inexpensive multi-elemental analysis. LIBS has been used for verification of authenticity and fraud detection in food. With the globalisation of food markets, food authentication has become a significant concern worldwide to ensure food safety and to avoid origin and quality fraud. A multi-elemental fingerprint is a powerful tool for detection of adulterants and geographical origin of foods. Laser-induced breakdown spectroscopy (LIBS) is a promising technique that can provide a mineral fingerprint of food products. LIBS allows a rapid, high-throughput, micro-destructive and multi-elemental analysis of a wide range of samples type. It has already been demonstrated by several authors that LIBS can be successfully used for food authentication. Although LIBS shows excellent potential for at-line or portable applications, improvement in sensitivity of trace elements detection, sample preparation, data analysis and instrument miniaturisation are needed.